If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B + -2(1 + 3b) = 4b + -29 B + (1 * -2 + 3b * -2) = 4b + -29 B + (-2 + -6b) = 4b + -29 Reorder the terms: -2 + B + -6b = 4b + -29 Reorder the terms: -2 + B + -6b = -29 + 4b Solving -2 + B + -6b = -29 + 4b Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '2' to each side of the equation. -2 + B + 2 + -6b = -29 + 2 + 4b Reorder the terms: -2 + 2 + B + -6b = -29 + 2 + 4b Combine like terms: -2 + 2 = 0 0 + B + -6b = -29 + 2 + 4b B + -6b = -29 + 2 + 4b Combine like terms: -29 + 2 = -27 B + -6b = -27 + 4b Add '6b' to each side of the equation. B + -6b + 6b = -27 + 4b + 6b Combine like terms: -6b + 6b = 0 B + 0 = -27 + 4b + 6b B = -27 + 4b + 6b Combine like terms: 4b + 6b = 10b B = -27 + 10b Simplifying B = -27 + 10b
| 4cos(x)= | | (5b-7)-2(2b+4)=-4 | | (3u+8)5= | | -2(x+5)=-2(x-2)+5 | | lnx=-4.3 | | 5(x-1)-15=3(x+2)+4 | | 2y^2+3y-3=0 | | 7(5+4)= | | 1.5q=-4.8 | | m-3k=pfork | | g-7=22 | | 4(x+3)+6=4x+9 | | 2x+z=6 | | -x+y=zforx | | 4(x+3)+3x=7x+12 | | 11d+6=3d+62 | | -4=-2x-3 | | 2x+z+0=6 | | 4x+16-3x=-2-13 | | 6(x+3)+x=7x+9+9 | | 0=12x+x^2+36 | | 4x-16=x+2 | | 13-(4m+3)=2+2m-6 | | -8-12=4x+14-3x | | 5x^2+6xy+5y^2=8 | | 17-7x=-11 | | 8n+-9=-10 | | 52-26= | | 6(x+3)+x=6x+3+15 | | 6x+10-5x-1= | | -9x+9+10x=18 | | 81=6x-15 |